Evaluation of CD47 in the Suppressive Tumor Microenvironment and Immunotherapy in Prostate Cancer - Qianqian Wang; Chunxaing Feng; Yuchun Chen; Tianming Peng; Yong Li; Kunlin Wu; Xiaoyong Pu; Hanzhong Chen; Jiumin Liu (Journal of Immunology Research)
Background. CD47 has high levels of expression in malignant cancer cells, which binds to SIRP-α to release the “don’t eat me” signal and prevents mononuclear macrophages from phagocytosing the cells. Resistance to drugs and metastases are potential barriers for prostate cancer endocrine therapy. Although immunotherapy for tumors has developed rapidly in the last few decades, its effectiveness in treating prostate cancer is unsatisfactory. Prostate cancer has a high-expression level of CD47. Therefore, a novel approach for potential immunotherapy may be provided by investigating the relationship among CD47 and the infiltration of immune cells in the prostate carcinoma. Methods. The GEPIA database was utilized to compare the abundance of CD47 in malignant tissues with tissues that were normal. Furthermore, the function of CD47 in prostate carcinoma was assessed by CancerSEA. The association among CD47 and the tumor microenvironment was assessed utilizing the TISCH single cell data database. By using TIMER, the connection among CD47 and immunological invasion of prostate cancer was explored. Moreover, macrophages were cocultured with mouse prostate cancer cell RM-1 blocked by CD47 antibody to observe the changes in phagocytosis efficiency in vitro. Results. Expression level of CD47 is upregulated in prostate carcinoma, and it is closely connected with prostate cancer’s inadequate immune invasion. CD47 antibody blocking promotes macrophage phagocytosis of RM-1. Conclusion. Our research demonstrates a closely relationship among CD47 and the immunological microenvironment of prostate cancer, and blocking CD47 can promote macrophages to phagocytosis of prostate cancer cells. Therefore, CD47 may provide novel strategies for potential immunotherapy of prostate cancer.